A review of the genus Bruchia Weise 1906 (Coleoptera: Chrysomelidae: Cassidinae) - Staines, C. L. (Zootaxa, 2007)
The species of Bruchia are reviewed. Bruchia armata from Brazil, Colombia and Peru, and B. scapularis from Colombia are described as new. Each species is described and illustrated and a key to the species is provided.